Design and implementation of a cohort‐based undergraduate research experience in the agricultural sciences. Issue 1 (11th May 2022) - Maaz, Tai McClellan; Nguyen, Nhu H.; Del Valle Echevarria, Angel R.; Kantar, Michael B.; Mileyko, Yuriy; Muszynski, Michael G.
Abstract: Science, technology, engineering, and mathematics (STEM) education is consistently seen as a top priority; however, STEM programs often suffer from low retention. Students who start in STEM degree programs often lose interest or face obstacles that cause them to leave. Here, we describe a non‐traditional approach meant to encourage a range of students to pursue or continue their STEM education. Active learning approaches have long been touted to stimulate long‐term interest and prepare students for a career in natural science. We provide a case study of an interdisciplinary, cohort‐centric, mentor‐guided summer research internship. By establishing an understanding of how science is currently conducted in agriculture, through several faculty mentors, the program allowed students to embrace their core interests while being able to fit into larger interdisciplinary narratives which provided motivation to continue their path in STEM education. Core Ideas: A cohort‐based undergraduate research experience differs from the typical apprentice‐based models. Generating data together and asking questions from diverse perspectives allows students to work across scales. Creating interdisciplinary teams allows students to participate in more realistic research for complex problem‐solving. A cohort‐based research experience provides enriching activities along the active learning continuum.